Fabrication of superhydrophobic surface with SILICA/PDMS nanocomposite using dip coating - Guptha, Myadam Rahul; Bora, Tanujjal; Ricco, Raffaele; Hornyak, Louis; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Silica (SiO2) is one of the very interesting inorganic compound materials which have unique physio-chemical properties and wide industrial applications. In this research we used silica nanoparticles surface modified with hydrophobic functional groups to prepare a nanocomposite using polydimethylsiloxane (PDMS) as matrix and use the nanocomposite to fabricate superhydrophobic surface using dip coating technique. The silica nanoparticles, silica/PDMS nanocomposite and the superhydrophobic surfaces are characterized by electron microscopy to study their morphology. Water contact angle on the superhydrophobic surface is studied by analysing surface wettability measurement methods. Static and Sliding water contact angles are investigated for different concentrations of silica nanoparticles in the nanocomposite. A water contact angle of 154 i̊s obtained for silica/PDMS nanocomposite film which is almost 28% higher than the plain PDMS indicating improved hydrophobicity of the PDMS layer.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Nanotechnology, School of Engineering and Technology
Research report (M. Eng.) - Asian Institute of Technology, 2022
Keywords: Coatings -- Additives; Silica -- Surfaces